2017
DOI: 10.18632/oncotarget.15884
|View full text |Cite
|
Sign up to set email alerts
|

MNS16A tandem repeat minisatellite of human telomerase gene: functional studies in colorectal, lung and prostate cancer

Abstract: MNS16A, a functional polymorphic tandem repeat minisatellite, is located in the promoter region of an antisense transcript of the human telomerase reverse transcriptase gene. MNS16A promoter activity depends on the variable number of tandem repeats (VNTR) presenting varying numbers of transcription factor binding sites for GATA binding protein 1. Although MNS16A has been investigated in multiple cancer epidemiology studies with incongruent findings, functional data of only two VNTRs (VNTR-243 and VNTR-302) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Hofer et al investigated promoter activity of all six known MNS16A VNTRs in different cell lines and showed the distribution of relative promoter activities of different MNS16A VNTRs determined by luciferase reporter assays. In all investigated cell lines, promoter activity of shorter constructs (also VNTRs-234) was higher than promoter activity of longer constructs, reflecting an indirect correlation between VNTR length and promoter activity 25. In addition, Zhang et al observed that carriers of the SL genotype had lower TERT expression compared to LL carriers when analyzing nasopharyngeal carcinoma tissue by immunohistochemical staining 26…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hofer et al investigated promoter activity of all six known MNS16A VNTRs in different cell lines and showed the distribution of relative promoter activities of different MNS16A VNTRs determined by luciferase reporter assays. In all investigated cell lines, promoter activity of shorter constructs (also VNTRs-234) was higher than promoter activity of longer constructs, reflecting an indirect correlation between VNTR length and promoter activity 25. In addition, Zhang et al observed that carriers of the SL genotype had lower TERT expression compared to LL carriers when analyzing nasopharyngeal carcinoma tissue by immunohistochemical staining 26…”
Section: Discussionmentioning
confidence: 93%
“…It has been demonstrated that TERT promoter activity depends on variable numbers of tandem repeats (VNTRs), such as MNS16A, which constitutes a binding site for a transcription factor GATA binding protein 1 (GATA-1) 24. Research on the functional significance of this genetic polymorphism showed that shorter MNS16A is related to higher TERT promoter activity 24,25. This functional polymorphism may play an important role in human longevity, disease progression and response to therapy of patients with non-Hodgkin’s B-cell lymphomas and the development of other cancers 2629…”
Section: Introductionmentioning
confidence: 99%
“…[16] This study showed the SS form of VNTR-243 was associated with an elevated risk of lung cancer. On the contrary, despite the fact that MNS16A polymorphic variation has been studied in numerous contexts related to a number of different cancers, [8,[21][22][23][24][25] results are conflicting, either due to ethnic variations or some other technical reasons. For example, a study conducted in China found no significant differences between MNS16A polymorphisms among pericentenarian and normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…[8] In addition, two other rare alleles, VNTR-272 and VNTR-333, were also found in cancer cell lines. Classification of VNTR-243 and VNTR-272 as short (S) alleles, and VNTR-302 and VNTR-333 as long (L) alleles, was introduced for the purposes of statistical analysis by Wang et al [21] The MNS16A variable number tandem repeat (VNTR) functional polymorphism has been investigated in various studies including nasopharyngeal carcinoma, [22] colorectal cancer, [8,23] lung cancer, [21,24] prostate cancer, [23,25] bladder cancer, [26] and in the normal human life span. [27] In this study, we aimed to determine whether the MNS16A VNTR polymorphism of the hTERT gene was associated with bladder cancer risk in a Kashmiri population.…”
Section: Openmentioning
confidence: 99%
“…They are known to modulate biologic processes, including gene expression and protein function [10][11][12][13][14]. These eVNTRs (VNTR expression Quantitative Trait Loci) also mediate risks of developing various cancers [15,16] including breast cancer [17][18][19][20]. A genome-wide investigation of VNTRs as modifiers has been hampered by technical difficulties; however, adVNTR [10,21] became available to genotype VNTRs (i.e., count repeat units) from next generation sequencing (NGS) data.…”
Section: Introductionmentioning
confidence: 99%